Scientific Literacy in Indonesian Secondary Education: Are We Ready to be Scientifically Literate Society? - Listiani Listiani (International Journal of STEM Education for Sustainability, 2025)
The curriculum in Indonesia plays a pivotal role in equipping students with scientific literacy. It is important to undertake an exhaustive examination of curriculum documents to gauge how much scientific literacy is embedded within the curriculum and how effectively it fosters such literacy. Thus, this research aims to elucidate the presence of scientific literacy dimensions within the educational framework of Indonesia, thereby reflecting the government’s commitment to nurturing scientifically literate societies. This study uses a qualitative approach to analyze Indonesian curriculum documents while employing data triangulation to ensure the research’s validity and credibility. The findings indicate that the competencies outlined in the curriculum align with the dimensions of scientific literacy. This suggests that the Indonesian curriculum is designed to cultivate scientifically literate communities. However, further studies are required regarding implementing scientific literacy in the classroom.